2011
DOI: 10.1007/s10554-011-9937-8
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection (un)awareness in cardiologists, and how to improve it

Abstract: In 2010 the International Atomic Energy Agency launched the "3 A's campaign": Audit, Appropriateness and Awareness for radiological justification, which is an effective tool for cancer prevention. Cardiologists prescribe the majority of radiological testing, but their awareness of doses and risks of ionizing cardiac imaging test is low. To assess radioprotection awareness of prescribing and practicing physicians (mainly cardiologists) before and after a radioprotection course. We held a 1-day 6-h primer of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Radiation reduction methods are outdated, and new proposals have been presented. [14][15][16][17][18] It has been stipulated that ionising radiation exposure should be as low as possible when it is inevitable. The "as low as reasonably achievable" (ALARA) principle, 19,20 established in 1977, essentially states that radiation exposure should be kept as low as reasonably achievable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation reduction methods are outdated, and new proposals have been presented. [14][15][16][17][18] It has been stipulated that ionising radiation exposure should be as low as possible when it is inevitable. The "as low as reasonably achievable" (ALARA) principle, 19,20 established in 1977, essentially states that radiation exposure should be kept as low as reasonably achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medical societies are encouraging more training programs and education measures to reduce the biological risks. 1,16,17 The area exposed to biological radiation effects and the potential stochastic risks of neoplasia are as important as the total radiation dose. The present study demonstrated that there is a strong relation between the total received dose and the irradiated area, regardless of the patient's weight.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the level of awareness is critical to identify any de&iciencies in order to overcome them and eventually reduce radiation hazards to all who are involved in the process of radiologic examination. Unfortunately, several studies have assessed this level and most of them reported signi&icant inadequacy (10,(12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that have evaluated the awareness and knowledge of expected radiation doses and associated risks among physicians, radiologists, and patients from different backgrounds and educational levels. Most of the reported results indicated a significant underestimation of radiation dose and its risks among patients [10][11][12][13][14][15][16][17]. The knowledge and awareness of the radiation doses and risks can help in making decisions regarding the frequency of scans [18].…”
Section: Introductionmentioning
confidence: 99%